Characterization and Classification of Keratinized Odontogenic Cysts in 29 Dogs. (June 2022) - Johnson, Jessica; Scott, Kristin; Bell, Cynthia M.
This retrospective case series presents a unique group of odontogenic cysts that are lined by heavily keratinized epithelium and contain laminated keratin. Keratinized odontogenic cyst (KOC) is proposed as appropriate terminology for the described lesions. The series evaluates cysts from 29 dogs, including clinical presentation, diagnostic imaging, and histopathology. All 29 lesions occurred in tooth bearing regions of the jaws; 21 were maxillary and 8 were mandibular. These keratinized odontogenic cysts were unilocular or multilocular, and some demonstrated considerable expansion resulting in bone destruction. In 13 of 29 cases, there was evidence of tooth displacement associated with the expansion of the KOC. The KOCs did not have a distinctive radiographic appearance. 48% of the cysts had a soft tissue defect through which the keratin contents could be visualized. Cyst contents ranged from hard mineralized keratin to fluid consistency with soft flecks of keratin. The pathoetiology of KOCs is unknown; however, the biological behavior is benign and thought to be slowly progressive despite potential for locally destructive growth. Recurrence is uncommon when cyst enucleation and debridement are aggressive or when solid cysts are excised en bloc.